ANALISIS INDUSTRI MINUMAN KESEHATAN DI INDONESIA - Samuel Wirawan (Center for Economic Studies Universitas Katolik Parahyangan, 2006)
Energy drink is a new product among the consumer goods in Indonesia. This product was developed in Indonesia in the middle of the 80's. The popularity of this energy drink grew quickly and people fond of drinking it. The popularity could grow quickly because the producer of the energy drink did a lot of promotions, both written and electronically. The producer was trying to make a brand image that energy drink was the symbol for strength and vitality for those who drink it.This industrial analysis is discussed from several factors such as market structure, conduct, performance, condition in Indonesia, and player’s behavior and pricing strategy. This analysis is discussed in economic managerial.